UMP and Vacuumschmelze VAC signed MoU on sharing of technology and talent development - Mohamed Rafiee, Kamarudin (2021)
PEKAN, 8 November 2021 – Universiti Malaysia Pahang (UMP) and Vacuumschmelze (VAC) signed a Memorandum of Understanding (MoU) that combined innovative strengths and capabilities of a well-established university with a German-based advanced magnetic solutions company in Malaysia.